2018
DOI: 10.1097/ncc.0000000000000538
|View full text |Cite
|
Sign up to set email alerts
|

Typologies for Restructuring Relationships in Cancer Survivorship

Abstract: Appropriate clinical nursing processes and tailored interventions are required to support cancer survivors and promote engagement with self-management practices. Nurses are a vital component of the social support that enables patients to make the best health and lifestyle choices available to them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 47 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…Whilst the studies that were included in this review shed light on some of the self-management experiences within a rural-urban setting, they are from countries with different healthcare systems and services in comparison with the UK, thus warranting further investigation in a UK setting. Despite the increasing body of work that explicitly focuses on selfmanagement and cancer within a UK context [13,17,18,[51][52][53][54], there are no studies that have reported data on ruralurban residency in relation to this. Equally, research comparing outcomes between rural and urban people affected by cancer has tended to focus on the post-diagnosis stages, as well as survival rates, and has yet to examine the influence of residency on longer-term survivorship outcomes, such as self-management post-treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the studies that were included in this review shed light on some of the self-management experiences within a rural-urban setting, they are from countries with different healthcare systems and services in comparison with the UK, thus warranting further investigation in a UK setting. Despite the increasing body of work that explicitly focuses on selfmanagement and cancer within a UK context [13,17,18,[51][52][53][54], there are no studies that have reported data on ruralurban residency in relation to this. Equally, research comparing outcomes between rural and urban people affected by cancer has tended to focus on the post-diagnosis stages, as well as survival rates, and has yet to examine the influence of residency on longer-term survivorship outcomes, such as self-management post-treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Structured and organized social support and social relationships between cancer survivors and their supporters have an impression of their health and ability to fix self-management practices. Enhances their engagement with health-promoting practices and connects cancer patients within future life aspects [ 10 ]. Social support is crucial for improved quality of life of patients with a chronic disease like cancer.…”
Section: Introductionmentioning
confidence: 99%